Functioning of the Lexical Units Denoting Virtual Space Notions in Modern Ukrainian Language (Linguostylistic Studies, 2016)
The article analyzes the loci-nominations used to describe objects of virtual space in modern Ukrainian language. It reveals and determines the internal lexical-semantic relationships and differentiation between them within the semantic field of «virtual space». The emphasis is laid on the classification of the lexical units which represent the following lexical-semantic groups: «Virtual mythological space», «Virtual artistic space», «Virtual inner psychological space», «virtual space of dreams», «virtual gaming space», «virtual space of computer technologies». The article reveals the functioning peculiarities of loci denoting objects of virtual space in modern Ukrainian literary language. It has been proved that these peculiarities depend on the style of the source they are used in. Special attention is paid to the facts of figurative transference of space names depending on their use in the texts of different styles. Key words: lexical semantics, locus, lexical-semantic group, virtual space. References